MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN LAYANAN PENDIDIKAN BERMUTU DI TK ANAK CERIA - Deni Tirta Pawana Putra; Elistiana Wulan Sari; Eneng Robi’ah; Waska Warta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of School-Based Management(SBM) at TK Anak Ceria, identify factors that support or hinder the process, andevaluate its impact on educational service quality. A descriptive qualitative approachwas applied, using data from observations, interviews, questionnaires, documentanalysis, focus group discussions (FGD), and extracurricular activity reviews. Theresults show that SBM is carried out through a participatory approach, with theinvolvement of the principal, teachers, and some parents in school managementand decision-making. Supporting factors include transparent leadership, teacherparticipation in planning, and a conducive learning environment. Barriers identifiedare limited educational tools, inadequate teacher training, and low parentalinvolvement in school program design. Overall, SBM contributes positively toimproving education quality, though improvements are still needed in extracurricularprograms, parental engagement, and teacher development. These findings canserve as a useful reference for schools, committees, and policymakers in enhancingSBM practices for early childhood education.